Diet, Protein, Iron and Vitamin C Intake on Anemia Status of Adolescent Girls - Yanti, Sriwiyanti; Sari, Yestina Agusti Permata; Meilina , Ayu (Chakra Brahmanda Lentera Institute, 2024)
Background: Anemia is a condition of the body in which the level of Hemoglobin (Hb) in the blood is below normal. Anemia in adolescents has an impact on decreased concentration, memory, and brain performance in adolescents, as well as stunted physical growth, first menstruation, decreased immunity and learning achievement. Objective to find out whether there is a relationship between diet, protein intake, iron intake and vitamin C intake on the anemia status of adolescent girl Methods: This research was conducted in May 2023. This type of research is a descriptive study with a cross-sectional research design. The sample size in this study was 70 respondents. The data for this research were taken by direct interviews using a questionnaire and a 3 × 24 hour Recall form with the results of Univariate and Bivariate data Results: The results of the study with univariate analysis showed that 4 students (5.7%) had anemia status. A good diet was 85.7%, protein intake was insufficient by 88.6%, iron intake was insufficient by 87.1%, and vitamin C intake was insufficient by 97.1%. The results of the cross-table analysis showed that female students with anemia had a poor diet of 75%, protein intake was 100%, iron intake was 100% insufficient, and vitamin C intake was insufficient by 100%. Conclusion: Bivariate analysis shows an F change value of 0.000 (<0.05) meaning there is a significant relationship between the variables of diet, protein intake, iron intake and vitamin C intake on the anemia status of young women, and this relationship shows an R value: 0.603 meaning a relationship between the independent variables and the dependent variable is strong.